(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The research aims at determine the gender and the features of the characters in children’s programs on CN. We chose an analytical descriptive approach that relies on content analysis as a research tool.To achieve that a content analysis form was applied on a sample of (295) programs. Results were as following: 1- The most common subjects in CN programs were the social subjects, and the fiction subjects. 2- The most common language was the classical Arabic. 3- Most programs on CN were foreign. 4- The most common gender was the male relatively (%53.81). 5- the most common features of male characters were: the fashionable look, happy and joy, strong and supernatural power. 6 - The most common features of female characterswere: the fashionable look, happy and joy, the self-confidence.